2014
DOI: 10.1021/jp501210d
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Theoretical Study on the Formation of 2-Methylnaphthalene (C11H10/C11H3D7) in the Reactions of the Para-Tolyl (C7H7) and Para-Tolyl-d7 (C7D7) with Vinylacetylene (C4H4)

Abstract: We present for the very first time single collision experimental evidence that a methyl-substituted polycyclic aromatic hydrocarbon (PAH)-2-methylnaphthalene-can be formed without an entrance barrier via indirect scattering dynamics through a bimolecular collision of two non-PAH reactants: the para-tolyl radical and vinylacetylene. Theory shows that this reaction is initiated by the addition of the para-tolyl radical to either the terminal acetylene carbon (C(4)) or a vinyl carbon (C(1)) leading eventually to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…The reaction leading to indene has an entrance barrier of about 14 kJ mol À1 , while the reactions of phenyl radicals with vinylacetylene and 1,3-butadiene involve submerged barriers implying naphthalene (C 10 H 8 ) and 1,4-dihydro-naphthalene (C 10 H 10 ) can be formed in low temperature interstellar environments, as low as 10 K, such as in molecular clouds. 32 Here, we expand these studies and apply crossed molecular beams and ab initio calculations to investigate the formation routes of methylsubstituted PAHs through the use of methyl-substituted aromatic radicals. [21][22][23] Recent studies in our group provide compelling evidence of the formation of dimethyldihydronaphthalenes via the reaction of the para-tolyl radicals (C 6 H 4 CH 3 ) with isoprene (C 5 H 8 ); 15 subsequent studies also proposed a novel route to form methylsubstituted naphthalene via the reaction of the para-tolyl radicals (C 6 H 4 CH 3 ) with vinylacetylene (CH 2 CHCCH).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction leading to indene has an entrance barrier of about 14 kJ mol À1 , while the reactions of phenyl radicals with vinylacetylene and 1,3-butadiene involve submerged barriers implying naphthalene (C 10 H 8 ) and 1,4-dihydro-naphthalene (C 10 H 10 ) can be formed in low temperature interstellar environments, as low as 10 K, such as in molecular clouds. 32 Here, we expand these studies and apply crossed molecular beams and ab initio calculations to investigate the formation routes of methylsubstituted PAHs through the use of methyl-substituted aromatic radicals. [21][22][23] Recent studies in our group provide compelling evidence of the formation of dimethyldihydronaphthalenes via the reaction of the para-tolyl radicals (C 6 H 4 CH 3 ) with isoprene (C 5 H 8 ); 15 subsequent studies also proposed a novel route to form methylsubstituted naphthalene via the reaction of the para-tolyl radicals (C 6 H 4 CH 3 ) with vinylacetylene (CH 2 CHCCH).…”
Section: Introductionmentioning
confidence: 99%
“…Note that these pathways involve moderate barriers to addition of magnitude 8−9 kJ mol −1 , which are slightly above the energies of the separated reactants. However, within the accuracy of our calculations of ±10 kJ mol −1 , this barrier might drop below the energies of the separated reactants, possibly resulting in a submerged barrier as seen for the phenyl−vinylacetylene, 21 4-tolyl−vinylacetylene, 26 and phenyl −1,3-butadiene 44 systems. These intermediates can either undergo unimolecular decomposition by eliminating an atomic hydrogen and/or a methyl group or isomerize prior to further decomposition.…”
Section: Theoretical Resultsmentioning
confidence: 70%
“…23,24 Experiments carried out under bulk conditions showed that the reaction of the C 7 H 7 radical with the methyl radical produces styrene (C 8 H 8 ) and molecular hydrogen. 25 However, with the exception of the reaction of 4-tolyl (p-tolyl) radicals with vinylacetylene (C 4 H 4 ), which leads to the formation of 2-methylnapthalene, 26 reactions of any C 7 H 7 isomer with unsaturated hydrocarbons under single collision conditions have been elusive. In this paper, we report on the reaction of the 4-methylphenyl (4-tolyl) radical with 1,2-butadiene [H 2 CCCH(CH 3 )] and elucidate to what extent substituted PAHs can be formed under single collision conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Bicyclic aromatic molecules and their methyl-substituted counterparts formed in exoergic and de facto barrierless bimolecular reactions of phenyl-type radicals with vinylacetylene (C 4 H 4 ), 1,3-butadiene (C 4 H 6 ), and 1-/2-methyl-1,3-butadiene (C 5 H 8 ): (6) naphthalene (C 10 H 8 ; phenyl-vinylacetylene), (7) 1-methylnaphthalene (C 10 H 7 CH 3 ; meta-tolyl-vinylacetylene), (8) 2-methylnaphthalene (C 10 H 7 CH 3 ; meta/para-tolyl-vinylacetylene), (9) 1,4-dihydronaphthalene (C 10 H 10 ; phenyl-1,3-butadiene), (10) 9-methyl-1,4-dihydronaphthalene (C 10 H 9 CH 3 ; meta-tolyl-1,3-butadiene), (11) 8-methyl-1,4-dihydronaphthalene (C 10 H 9 CH 3 ; meta/para-tolyl-1,3-butadiene), (12) 1-methyl-1,4-dihydronaphthalene (C 10 H 9 CH 3 ; phenyl-1-methyl-1,3-butadiene), and (13) 2-methyl-1,4-dihydronaphthalene (C 10 H 9 CH 3 ; phenyl-2-methyl-1,3-butadiene) (83,(90)(91)(92).…”
Section: Figurementioning
confidence: 99%